Regional and temporal variations in tissue sodium concentration during the acute stroke phase - Wetterling, Friedrich (Magnetic resonance in medicine, 2012)
Abstract A technique for noninvasively quantifying the concentration of sodium (23Na) ions was applied to the study of ischemic stroke. 23Na?magnetic resonance imaging techniques have shown considerable potential for measuring subtle changes in ischemic tissue, although studies to date have suffered primarily from poor signal/noise ratio. In this study, accurate quantification of tissue sodium concentration (TSC) was achieved in 23Na images with voxel sizes of 1.2 ?L acquired in 10 min. The evolution of TSC was investigated from 0.5 to 8 h in focal cortical and subcortical ischemic tissue following permanent middle cerebral artery occlusion in the rat (n = 5). Infarct volumes determined from TSC measurements correlated significantly with histology (P = 0.0006). A delayed linear model was fitted to the TSC time course data in each voxel, which revealed that the TSC increase was more immediate (0.2 ± 0.1 h delay time) in subcortical ischemic tissue, whereas it was delayed by 1.6 ± 0.5 h in ischemic cortex (P = 0.0002). No significant differences (P = 0.5) were measured between TSC slope rates in cortical (10.2 ± 1.1 mM/h) and subcortical (9.7 ± 1.1 mM/h) ischemic tissue. The data suggest that any TSC increase measured in ischemic tissue indicates infarction (core) and regions exhibiting a delay to TSC increase indicate potentially salvageable tissue (penumbra). Magn Reson Med, 2012. ? 2011 Wiley Periodicals, Inc.
First published: 15 June 2011
Gesehen am 16.04.2018